Unconventional Materials Usage in Design of Vehicle Bodies - Raz, Karel; Hora, Jan; Pavlata, Petr (Manufacturing Technology Journal, 2017)
This article deals with unconventional materials usage in design of vehicle bodies. Main focus is on sandwich materials (with honeycomb structure) for walls of the main body. These panels are designed from polypropylene. Joining of theses sandwich panels is also solved here by special aluminium profile. Virtual simulations and stress evaluation are used methods for design evaluating. Research is focused also on material properties testing. Tested are sandwich materials and also connecting aluminium profiles. All material properties and testing principles are here clearly described. Lower weight of vehicle body leads to possibility of floor optimization. Welded frame of floor can be lighter and strength of floor is also evaluated here. All these steps lead to lighter design with economic benefits for producer.
Keywords: Sandwich structures; Polypropylene; Stress; Vehicle body